Temporary Biliary Stent Placement for Benign Stricture with Laparoscopic-Assisted Endoscopic Stent Retrieval in a Patient Status Post Roux-en-Y Gastric Bypass: A Multidisciplinary Approach to a Complex Condition - Anton, Kevin; Khara, Harshit S.; Bhanushali, Ashok B. (Journal of Clinical Interventional Radiology ISVIR, 2017)
Benign biliary strictures are multifactorial in etiology and can be difficult to treat, causing significant morbidity and mortality. In patients with prior upper gastrointestinal surgery, such as Roux-en-Y gastric bypass, options for intervention are limited by the inability of an endoscope to reach the biliary ductal system due to altered anatomy. In patients with an inaccessible ductal system by endoscopic retrograde cholangiopancreatography (ERCP), percutaneous bile duct stent placement for benign strictures has traditionally been reserved for cases of failed cholangioplasty without additional surgical options. Our case details a novel multidisciplinary management approach for the treatment of a refractory biliary stricture in a patient with Roux-en-Y gastric bypass anatomy with remnant gastrectomy. Following interventional radiology-guided retrievable biliary stent placement and subsequent remodeling, laparoscopy-assisted ERCP with stent retrieval was performed through the combined efforts of minimally invasive surgery and gastroenterology.
Keywords: biliary stricture; biliary stent; cholangioplasty